Identifying Frailty and its Outcomes in Older People in Rural Tanzania. Issue 3 (27th May 2017) - Gray, William K.; Orega, Golda; Kisoli, Aloyce; Rogathi, Jane; Paddick, Stella-Maria; Longdon, Anna R.; Walker, Richard W.; Dewhurst, Felicity; Dewhurst, Matthew; Chaote, Paul; Dotchin, Catherine
Abstract : Background/Study Context : Interest in frailty is growing in low- and middle-income countries, due to demographic aging and resource limitations. However, there is a paucity of data on the nature of frailty in Africa. Methods : The study collected frailty data from people aged 70 years and over living in six villages in the rural Hai District of northern Tanzania. At baseline, a limited data set was collected for 1198 people and a more comprehensive data set for a stratified sample of 296 people. A 40-item frailty index was constructed. Data regarding mortality and dependency were collected at 3-year follow-up. Results : A higher frailty index score was significantly correlated with greater age, never having attended school, falls, mortality, and dependency in activities of daily living. Logistic regression modeling revealed functional disability and cognitive function to be significant independent predictors of the outcome "mortality or dependency." Conclusions : In resource-poor settings, brief frailty screening assessments may be a useful way of identifying those most in need of support.